Interleukin-10-Modified Adipose-Derived Mesenchymal Stem Cells Prevent Hypertrophic Scar Formation via Regulating the Biological Characteristics of Fibroblasts and Inflammation - Fang Xie; Li Teng; Jianjian Lu; Jiajie Xu; Chao Zhang; Liya Yang; Xiaoyang Ma; Minghao Zhao (Mediators of Inflammation)
Hypertrophic scar causes serious functional and cosmetic problem, but no treatment method is known to achieve a satisfactory therapeutic effect. However, mesenchymal stem cells show a possible cure prospect. Here, we investigated the effect of interleukin-10-modified adipose-derived mesenchymal stem cells (IL-10-ADMSC) on the formation of hypertrophic scar. In vitro, IL-10-ADMSC could highly express IL-10 and exhibited stronger inhibition of hypertrophic scar fibroblasts (HSFs) proliferation, migration, and extracellular matrix synthesis (the expression of collagen I, collagen III, FN, and α-SMA protein) than ADMSC. In vivo, we found that IL-10-ADMSC speeded up wound healing time and reduced scar area and scar outstanding height. Same as in vitro, IL-10-ADMSC also exhibited stronger inhibition of extracellular matrix synthesis (the expression of collagen I, collagen III protein) in wound than ADMSC. In addition, we also found that IL-10-ADMSC is also a stronger inhibitory effect on inflammation in wound than ADMSC, and IL-10-ADMSC inhibited TGF-β/Smads and NF-κB pathway. In conclusion, IL-10-ADMSC demonstrated the ability to prevent hypertrophic scar formation. And its possible molecular mechanism might be related to IL-10-ADMSC inhibiting the proliferation and migration of the synthesis of extracellular matrix of HSFs, and IL-10-ADMSC inhibited the inflammation during the wound healing.